Resting-State Functional Connectivity Characteristics of Resilience to Traumatic Stress in Dutch Police Officers - Setroikromo, Santoucha N. W.; van der Werff, Steven J. A.; Smit, Annika S.; Vermetten, Eric; Van Der Wee, Nic J. A. (Frontiers in Behavioral Neuroscience, 2022)
Background: Insights into the neurobiological basis of resilience can have important implications for the prevention and treatment of stress-related disorders, especially in populations that are subjected to high-stress environments. Evaluating large scale resting-state networks (RSNs) can provide information regarding resilient specific brain function which may be useful in understanding resilience. This study aimed to explore functional connectivity patterns specific for (high) resilience in Dutch policemen after exposure to multiple work-related traumatic events. We investigated resting-state functional connectivity (RSFC) of the salience network (SN), limbic network and the default mode network (DMN). Methods: Resting-state functional MRI scans were obtained from trauma-exposed executive personnel of the Dutch police force and non-trauma exposed recruits from the police academy. Participants were divided in three groups: a resilient group (n = 31; trauma exposure; no psychopathology), a vulnerable group (n = 32; trauma exposure, psychopathology) and a control group (n = 19; no trauma exposure, no psychopathology). RSFC of the three networks of interest were compared between these groups, using an independent component analysis and a dual regression approach. Results: We found decreased resilience-specific positive RSFC of the salience network with several prefrontal regions. The DMN and limbic network RFSC did not show resilience-specific patterns. Conclusions: This study shows a differential RSFC specific for resilient police officers. This differential RSFC may be related to a greater capacity for internal-focused thought and interoceptive awareness, allowing more effective higher-order responses to stress in highly resilient individuals.